Ageing gracefully: physiology but not behaviour declines with age in a diving seabird. (12th August 2014) - Elliott, Kyle H.; Hare, James F.; Le Vaillant, Maryline; Gaston, Anthony J.; Ropert‐Coudert, Yan; Anderson, W. Gary
Summary: A higher proportion of long‐lived animals die from senescence than short‐lived animals, yet many long‐lived homeotherms show few signs of physiological ageing in the wild. This may, however, differ in long‐lived diving homeotherms that frequently encounter hypoxic conditions and have very high metabolic rates. To examine ageing within a long‐lived diving homeotherm, we studied resting metabolism and thyroid hormones ( N = 43), blood oxygen stores ( N = 93) and foraging behaviour ( N = 230) of thick‐billed murres ( Uria lomvia ). Because murres dive exceptionally deep for their size and have a very high metabolism, we expected that ageing murres would show signs of physiological senescence. We paid particular attention to resting metabolism as we argue that these maintenance costs reflect those experienced during deep dives. Blood oxygen stores (haematocrit), resting metabolic rate and thyroid hormone levels all declined significantly with age in incubating murres 3–30 years of age. In birds measured longitudinally 3 years apart, thyroid hormone levels and haematocrit were both significantly lower, suggesting progressive changes within individuals rather than selective disappearance of individuals with high metabolic rates. Within our longitudinal data set, we found no effect of age on dive depth, dive shape or behavioural aerobic dive limit. A meta‐analysis of changes in resting metabolism with age across 15 animal species demonstrated that such declines are pervasive across most of the kingdom. The rate of decline was highest in species with high energy expenditure supporting a linkage between metabolism and senescence. Physiological changes occurred in tandem with advancing age in murres, but offset each other such that there was no detectable decline in behavioural performance. Abstract : Lay Summary